Factors Effecting Internal Browning Disorder in Pineapples and Its Control Measures - Jakrapong Pimpimol; Jingtair Siriphanich (Agriculture and Natural Resources, 1993)
The influence of chemical compositions and fruit coating on internal browning disorder of pineapple cv. Smooth Cayenne and cv. Queen were studied. The pineapples were stored at 8 and 12 oC, the result showed that ascorbic acid content was apparently related to the development of the internal browning symptom in both cultivars. Fruit containing high ascorbic acid contents in juice (more than 8 mg/100 ml) developed slightly browning, but in fruits containing low ascorbic acid content (4-6 mg/100 ml juice) showed very severe browning. The titratable acidity, soluble solids content, phenolic content, phenylalanine ammonia lyase and polyphenol oxidase activities were not related to the development of the internal browning. The prediction of internal browning of pineapple by analysing ascorbic acid content in the fruit before storage at chilling temperature revealed that ascorbic acid content could be moderately used to predict the severity of internal browning symptom, especially in cv. Smooth Cayenne. On the other hand, cv. Queen had very low ascorbic acid content and developed very severe symptom in all fruits. However, in predicting the symptom development, one must considered the weather condition during the fruit development as well. The using of fruit coating could reduce internal browning symptom in both cultivars by 70-80%.